Averting a malaria disaster - White, NJ; Nosten, F; Looareesuwan, S; Watkins, WM; Marsh, K; Snow, RW; Kokwaro, G; Ouma, J; Hien, TT; Molyneux, ME; Taylor, TE; Newbold, CI; et al. (The Lancet (British edition), 1999)
As treatments loose their effectiveness, morbidity and mortality from malaria will inevitably continue to rise. The rationale for combining drugs with independent modes of action is examined.